Experiments on the Porch Swing Bearing of Michelson Interferometer for Low Resolution FTIR. (30th May 2013) - Välikylä, Tuomas; Kauppinen, Jyrki
Abstract : Porch swing bearing for the linear motion of the mirror in Michelson interferometer for mid-infrared low resolution Fourier transform spectrometer was studied experimentally using the modulation depth of the collimated laser beam. The mirror tilting was measured to be lower than 5 μ rad over 3 mm mirror travel using two different bearings assemblies. Additionally, the manufacturing tolerances of the bearing type were proved to be loose enough not to limit the interferometer application. These demonstrate that the porch swing without any adjustment mechanisms provides the sufficient motion linearity.